Mengoptimalkan Transformasi Digital melalui Kemampuan Organisasi, Pengembangan Kerangka Konseptual - Rorlen; Ekadjaja, Margarita; Bravo, Christiandinata Tjandra (Jurnal Manajemen dan Teknologi, 2026)
Digital transformation plays a crucial role in enhancing organizational efficiency and competitiveness. This study aims to identify the capabilities required by organizations to optimize the digital transformation process and develop a practical framework based on dynamic capability mechanisms. Data collected from 150 respondents involved in digital transformation across various sectors revealed seven key themes: Strategy and Ecosystem, Innovation Thinking, Digital Transformation Technologies, Data, Operations, Organizational Design, and Digital Transformation Leadership. The findings show that the success of digitalization depends on an organization's ability to manage technology, data, innovation, and leadership that adapts to change. The developed framework can be applied by organizations to design more effective strategies, focusing on managing disruptive technologies, maximizing data utilization, and fostering leadership that supports innovation, enabling organizations to overcome challenges during the digitalization process.